Uniform phosphorus doping of untapered germanium nanowires. (31st October 2016) - Guilloy, K; Pauc, N; Gentile, P; Robin, E; Calvo, V
Abstract: One of the major challenges in the growth of vapor–liquid–solid (VLS) nanowires is the control of dopant incorporation in the structures. In this work, we study the n-type doping and morphology of nanowires grown by chemical vapor deposition when HCl is introduced. We obtain fully untapered nanowires with a growth temperature up to 410 °C and measure their resistivity using the 4-probe technique to be 2.0 mΩ cm. We perform energy dispersive x-ray measurements showing a concentration of dopants in the (5–7) × 10 18 cm −3 range, being radially and axially uniform. The combination of these two measurements shows that the mobility is the same as for bulk germanium, demonstrating that the VLS mechanism has no detrimental effect for the electron transport in these nanowires.